Media “Teka-Teki Silang” Implementasi Metode Design Thinking Dalam Pembelajaran Bahasa Indonesia Kelas VIII SMP Negeri 8 Palembang - R, Rohani; Agustina, Juaidah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Learning media is important to attract attention and create active interaction of students in the learning process so that learning activities will be effective and efficient. The selection of learning media before being applied must be selected according to the needs of students so that the learning process will be easier to achieve the desired goals. In this study, the selection of learning media to be used was selected according to the Design Thinking method. Design thinking is a problem-solving design innovation. The Design Thinking method goes through five stages: empathize, define, ideation, prototype and test. With the initial activity of finding the source of the problem, creating a model design, solving the problem with a prototype and at the end of the activity finding a new innovation that is appropriate as a form of solution to the existing problem by implementing the